1974
DOI: 10.1126/science.185.4151.614
|View full text |Cite
|
Sign up to set email alerts
|

Sex Pheromones and Reproductive Isolation of the Lesser Peachtree Borer and the Peachtree Borer

Abstract: (E,Z)-3,13-octadecadien-1-ol acetate, and (Z,Z)-3,13-octadecadien-1-ol acetate, isolated from the female lesser peachtree borer, Synanthedon pictipes (Grote and Robinson), and the female peachtree borer, Sanninoidea exitiosa (Say), respectively, strongly attract the respective males of these species in field bioassays. These compounds are the largest pheromones isolated thus far from a lepidopterous species. Sanninoidea exitiosa males did not respond to the synthesized (E,Z)-isomer, and low concentrations of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
65
2

Year Published

1974
1974
2012
2012

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(68 citation statements)
references
References 13 publications
1
65
2
Order By: Relevance
“…For example, male codling moth Cydia pomonella (L.) (Lepidoptera: Tortricidae) responded to wax droplets in a manner consistent with competitive attraction at low density, but appeared to have become desensitized when wax droplet density was increased greatly (Miller et al, 2006b). The high density that we used, 371 dispensers per hectare, is much lower than that used with codling moth, but peachtree borer is extremely responsive to its pheromone (Tumlinson et al, 1974).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, male codling moth Cydia pomonella (L.) (Lepidoptera: Tortricidae) responded to wax droplets in a manner consistent with competitive attraction at low density, but appeared to have become desensitized when wax droplet density was increased greatly (Miller et al, 2006b). The high density that we used, 371 dispensers per hectare, is much lower than that used with codling moth, but peachtree borer is extremely responsive to its pheromone (Tumlinson et al, 1974).…”
Section: Discussionmentioning
confidence: 91%
“…Since the identification of (Z,Z)-3,13-octadecadienyl acetate as the pheromone of peachtree borer (Tumlinson et al, 1974), a number of studies have documented successful disruption of peachtree borer orientation to pheromonebaited traps, as well as reduction in pest density, through the use of synthetic sources of pheromone (McLaughlin et al, 1976;Snow, 1990). However, mating disruption to control peachtree borer has not been adopted widely, in part, because of pheromone cost and the labor involved in deploying dispensers.…”
Section: Introductionmentioning
confidence: 99%
“…Since the pheromone study of Synanthedon exitiosa, 14) Z3,Z13-18:OAc has been identified from seven other sesiid species, indicating Z3,Z13-18:OAc to be the most common component of the sesiid pheromones. 7,8) The females of S. exitiosa and C. mimosa interestingly secrete this acetate as a single-component pheromone, while the others use a multi-component pheromone.…”
mentioning
confidence: 99%
“…The diyne (7) was partially hydrogenated over palladiumbarium sulfate in the presence of quinoline to give the desired (Z,Z)-olefin (8). Acetylation of the alcohol (8) with acetic anhydride in pyridine gave one of the desired products, (Z,Z)-3,13-octadecadienyl acetate (1).…”
mentioning
confidence: 99%